Basic science and spine literature document bone morphogenetic protein increases cancer risk - Epstein, Nancy E. (Surg Neurol Int, 2014)
BACKGROUND: Increasingly, clinical articles document that bone morphogenetic protein (BMP/INFUSE: Medtronic, Memphis, TN, USA) and its derivatives utilized in spinal surgery increase the risk of developing cancer. However, there is also a large body of basic science articles that also document that various types of BMP and other members of the TGF-Beta (transforming growth factor beta) family promote the growth of different types of cancers. METHODS: This review looks at many clinical articles citing BMP/INFUSE's role, largely “off-label”, in contributing to complications encountered during spinal surgery. Next, however, specific attention is given to the clinical and basic science literature regarding how BMP and its derivatives (e.g. members of the TGF-beta family) may also impact the development of breast and other cancers. RESULTS: Utilizing BMP/INFUSE in spine surgery increased the risk of cancers/new malignancy as documented in several studies. For example, Carragee et al. found that for single-level instrumented posterolateral fusions (PLF) using high-dose rhBMP-2 (239 patients) vs. autograft (control group; n = 224), the risks of new cancers at 2 and 5 years postoperatively were increased. In laboratory studies, BMP's along with other members of the TGF-Beta family also modulated/contributed to the proliferation/differentiation of breast cancer (e.g. bone formation/turnover, breast cancer-related solid tumors, and metastases), lung, adrenal, and colon cancer. CONCLUSIONS: BMP/INFUSE when utilized clinically in spinal fusion surgery appears to promote cancer at higher rates than observed in the overall population. Furthermore, BMP and TGF-beta are correlated with increased cancer growth both in the clinic and the laboratory.